Bis‐2(5H)‐furanone derivatives as new anticancer agents: Design, synthesis, biological evaluation, and mechanism studies. (25th March 2018) - Wu, Yan‐Cheng; Cao, Liang; Mei, Wen‐Jie; Wu, Han‐Qing; Luo, Shi‐He; Zhan, Hai‐Ying; Wang, Zhao‐Yang
Abstract : New bis‐2(5 H )‐furanone derivatives containing a benzidine core were synthesized via a one‐step transition‐metal‐free reaction of benzidine with 5‐substituted 3, 4‐dihalo‐2(5 H )‐furanones. Their antitumor activities against various tumor cells have been evaluated by MTT assay. Among them, compound4e exhibits significant inhibitory activity against C6 glioma cells with an IC50 value of 12.1 μm and low toxicity toward HaCaT human normal cells. Studies on the antitumor mechanism reveal that cell cycle arrest at S‐phase in C6 cells is induced by compound4e . Furthermore, investigations with electronic, fluorescence emission and circular dichroism spectra show that compound4e can significantly interact with C6‐DNA. These data indicate that DNA may be one of the potential targets for bis‐2(5 H )‐furanone derivatives as anticancer drugs. Abstract : The bis‐2(5 H )‐furanone derivatives containing a benzidine core are designed and easily obtained via a one‐step transition‐metal‐free reaction, which develops new chemical scaffolds with significant inhibitory activity against C6 glioma cells via binding C6‐DNA.